Disruptive Technology as an Enabler of the Circular Economy: What Potential Does 3d Printing Hold? - Garmulewicz, A (SAGE Publications Ltd, 2018)
Three-dimensional (3D) printing has been widely identified as an emerging disruptive technology. This study examines how this technology could enable the circular economy by disrupting the existing materials value chain. Specifically, could this novel technology be used to locally manufacture new goods from local sources of recycled plastic waste, thereby offering benefits for the efficiency and effectiveness of materials cycling? This article uses the London metropolitan area—where system conditions already exist in the form of material flows, technology policy, and facilities—in order to assess 3D printing’s viability as an enabler of a circular economy at the local level. An analysis of stakeholder perceptions identifies economic, technological, social, organizational, and regulatory barriers to mainstream implementation, and their likelihood of being overcome. © 2018, © The Regents of the University of California 2018.